A conserved HLA‐A*02:28 associated HLA haplotype, A*02:28‐B*15:11‐DRB1*09:01, restricted to Taiwanese. (25th October 2012) - Yang, K. L.; Lee, S. K.; Lin, P. Y.
Summary HLA‐A*02:28, found in a Korean and a Japanese, was reported independently to the IMGT/HLA database in 2003 and 2005, respectively. We report here eight Taiwanese unrelated bone marrow hematopoietic stem cell donors carrying A*02:28 detected during our routine HLA typing exercise. The probable HLA‐A, ‐B and ‐DRB1 haplotype in association with A*02:28 may be deduced from the eight marrow stem cell donor as A*02:28‐B*15:11‐DRB1*09:01. Our result suggests A*02:28‐B*15:11‐DRB1*09:01 is a conserved HLA haplotype restricted to Taiwanese.